Bi-Level Coordinated Operation Strategy of Multiple Microgrids in Multi-Time Scale. Issue 3 (7th February 2023) - Yang, Wenlin; Du, Pengcheng; Guo, Liang; Kou, Yan; Zhao, Xuanzong; Wang, Sen
Abstract: Microgrid (MG) has a significant effect on achieving local consumption of distributed renewable energy, power supply in remote areas, and so on. With the increasing number of MGs, the operation problem of multiple MGs has been more and more researched, while the coordinated operation and the bidding strategy are still the main problems limiting the development of multiple MGs. In this article, a bi-level optimization operation model of multiple MGs is studied. First, the multi-level control structure based on the multi-agent system and the multi-time scale optimization strategy framework of multiple MGs are constructed. The multi-level control structure is divided into three layers, including the device layer, MG layer, and power market layer. Second, the multi-time scale optimized operation model is established, including day-ahead model, intraday model, and real-time model. In addition, a game theory model is proposed to improve the interests or reduce costs of MGs. Finally, a case including three MGs is simulated and analyzed. The results show that the proposed multi-level structure of multiple MGs and multi-time scale optimization strategies are effective.